CT findings in dogs with gastric malposition: 6 cases (2016‐2019). (24th September 2020) - White, C.; Dirrig, H.; Fitzgerald, E.
Abstract : Objectives: To describe the computed tomographic (CT) findings of gastric malposition in a group of dogs with suspected chronic gastric instability. Materials and Methods: A multicentre retrospective study of CT studies of dogs with abnormal gastric position in the absence of clinical signs referable to gastric dilatation and volvulus. Results: Gastric malposition was identified in six dogs as either an incidental finding or in dogs with histories of chronic and intermittent gastroenteropathy. Gastric malposition was similar in all six cases; the pyloric canal was positioned in the left cranial abdomen in close proximity to the cardia and the pyloric antrum was found either to the left or ventral to the fundus. Clinical Significance: Recognition of gastric malposition as an incidental or chronic finding may prevent unnecessary emergency intervention on patients presenting for unrelated conditions.